2014
DOI: 10.1088/0004-637x/798/1/39
|View full text |Cite
|
Sign up to set email alerts
|

EARLY OBSERVATIONS AND ANALYSIS OF THE TYPE Ia SN 2014J IN M82

Abstract: We present optical and near infrared (NIR) observations of the nearby Type Ia SN 2014J. Seventeen optical and twenty-three NIR spectra were obtained from 10 days before (−10d) to 10 days after (+10d) the time of maximum B-band brightness. The relative strengths of absorption features and their patterns of development can be compared at one day intervals throughout most of this period. Carbon is not detected in the optical spectra, but we identify C I λ1.0693 in the NIR spectra. We find that Mg II lines with hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
108
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(126 citation statements)
references
References 73 publications
17
108
1
Order By: Relevance
“…4.4). We note that no LVG SNe in Benetti et al (2005) have v SiII ≥ 11 000 km s −1 around B-band maximum, but v SiII ≈ 11 750 km s −1 for SN 2014J at that epoch (Ashall et al 2014;Kawabata et al 2014;Marion et al 2015).…”
Section: Broad Lines Of Sn 2011fe and 2014jmentioning
confidence: 69%
See 1 more Smart Citation
“…4.4). We note that no LVG SNe in Benetti et al (2005) have v SiII ≥ 11 000 km s −1 around B-band maximum, but v SiII ≈ 11 750 km s −1 for SN 2014J at that epoch (Ashall et al 2014;Kawabata et al 2014;Marion et al 2015).…”
Section: Broad Lines Of Sn 2011fe and 2014jmentioning
confidence: 69%
“…The decline rate in this velocity (v SiII ) is calledv Si , and Maeda et al (2010a) Consulting the results of Kawabata et al (2014) and Marion et al (2015) for SN 2014J, we find thatv Si ∼55 km s…”
Section: Broad Lines Of Sn 2011fe and 2014jmentioning
confidence: 73%
“…Its expansion velocity decreases from 24,000 km/s in our first spectrum down to about 20,000 km/s in the spectrum 6 days later. In their study of near infrared spectra of SN 2014J, Marion, G. H. et al, (2015) found a similar behaviour for the Ca II IR triplet expansion velocities. They measured values for the high expansion velocity feature between 26,000 km/s and 20,000 km/s.…”
Section: Expansion Velocities Of Si II and Ca Iimentioning
confidence: 67%
“…This is not in contradiction, since strong resonance lines can extend to high velocities at early times, when the density is high in the outer ejecta. (Ashall et al 2014;Kawabata et al 2014;Tsvetkov et al 2014;Marion et al 2015); SN 2011fe: 1.11 ± 0.07 (Richmond & Smith 2012;Pereira et al 2013;McClelland et al 2013;Tammann & Reindl 2013) and different line and photospheric velocities, up to 1500 kms −1 around maximum, as shown in Fig 5. Neither SN 2011fe nor SN 2014J show traces of a single degenerate companion (Lundqvist et al 2015, but see also Graham et al 2015) favouring, in principle, the double degenerate scenario (see also Soker, García-Berro & Althaus 2014;Soker 2015). SN 2014J is highly reddened E(B − V) = 1.2 (Goobar et al 2014), while SN 2011fe is not, E(B − V) = 0.03 .…”
Section: P H Oto S P H E R I C V E L O C I T Y C O M Pa R I S O N Smentioning
confidence: 89%
“…modern SN Ia, SN 2014J has been extremely well observed: in γ -rays (Churazov et al 2014;Diehl et al 2014), X-rays (Margutti et al 2014), by Hubble Space Telescope Kelly et al 2014), optical (Amanullah et al 2014;Ashall et al 2014;Goobar et al 2014;Nielsen et al 2014) at high resolution (Welty et al 2014;Graham et al 2015;Jack, Baron & Hauschildt 2015;Ritchey et al 2015), near-infrared (near-IR; Friesen et al 2014;Marion et al 2015), mid-IR (Johansson et al 2014;Telesco et al 2015), polarimetry (Kawabata et al 2014), with rapid photometry (Siverd et al 2015), and in radio (Pérez-Torres et al 2014).…”
mentioning
confidence: 99%